THE ROLE OF LEADER IN BUILDING MULTICULTURAL ORGANIZATIONS - Rahadhini, Marjam Desma (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Multiculturalism include ideas, perspectives, policies, attitudes and actions by thediverse communities in terms of ethnicity, culture, religion, ideology and so forth;however aspires to develop the spirit of the same nationality and have pride to maintainplurality. It has two characteristics, namely the need for recognition and legitimacy ofcultural diversity. Multicultural society is a society that understands diversity in the lifeof the world and accept their diversity, such as: values, systems, culture, customs, andpolitical embraced. Leaders need to understand this diversity in creating a multiculturalorganization.In building a multicultural organization, leaders can use habituation andmodels, as well as education . Multicultural organizations can eliminate prejudice,improve the performance of members, optimize the potential of its members, and is ableto develop a family atmosphere to achieve long-term goals. The success of building amulticultural organization indicated internalized the existing programs thoroughly onevery member of the organization. Every leader needs to continue to build anorganization in a multicultural perspective.Keywords: leader, multicultural, organization, education, habituation